Ion-Pairing Reverse-Phase High Performance Liquid Chromatography Method for Simultaneous Estimation of Atenolol and Indapamide in Bulk and Combined Dosage Form - Baheti, K. G. (Medknow Publications & Media Pvt Ltd, 2012)
A sensitive, accurate, precise and validated ion-pairing reverse-phase liquid chromatographic method for the quantitative determination of atenolol and indapamide in bulk and tablet dosage form was developed. The proposed ion-pairing reverse-phase high performance liquid chromatography method utilises C(18) column with 5 μm, 150×4.6 mm i.d. column and mobile phase consisting of 0.1% w/v solution of octane sulphonic acid, sodium salt and methanol (55:45 v/v), (pH 2.8) and ultraviolet detection at 235 nm. A linearity range of 1-250 μg/ml and 1-25 μg/ml for atenolol and indapamide, respectively, was obtained. The mean recoveries are 100.48 and 99.82% for atenolol and indapamide, respectively. The method was validated as per International Conference on Harmonization guidelines.